2022
DOI: 10.3389/fphar.2022.781889
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxins in the Nervous System: Brighter Prospects for Neuroprotection

Abstract: Lipoxins (LXs) are generated from arachidonic acid and are involved in the resolution of inflammation and confer protection in a variety of pathological processes. In the nervous system, LXs exert an array of protective effects against neurological diseases, including ischemic or hemorrhagic stroke, neonatal hypoxia-ischemia encephalopathy, brain and spinal cord injury, Alzheimer’s disease, multiple sclerosis, and neuropathic pain. Lipoxin administration is a potential therapeutic strategy in neurological dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 146 publications
(211 reference statements)
0
10
0
Order By: Relevance
“…This may be due to the fact that the pharmacological targeting of the eicosanoid cascade often results in broad alterations across the entire AA metabolic network [63] with a blockade of the COX pathway often resulting in a shift towards the 5-LOX pathway [64,65]. Similarly, the inhibition of the 5-LOX pathway tends to cause available AA to shunt into the COX pathway and simultaneously prevent the formation of 12/15 HETE-derived lipoxins (LXs) which are critical for the resolution of inflammation [55,66,67]. Studies into the inhibition of more downstream COX and LOX enzymes have found a less considerable effect on AA cascade flux [63].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that the pharmacological targeting of the eicosanoid cascade often results in broad alterations across the entire AA metabolic network [63] with a blockade of the COX pathway often resulting in a shift towards the 5-LOX pathway [64,65]. Similarly, the inhibition of the 5-LOX pathway tends to cause available AA to shunt into the COX pathway and simultaneously prevent the formation of 12/15 HETE-derived lipoxins (LXs) which are critical for the resolution of inflammation [55,66,67]. Studies into the inhibition of more downstream COX and LOX enzymes have found a less considerable effect on AA cascade flux [63].…”
Section: Discussionmentioning
confidence: 99%
“…With MSU crystals triggering an inflammatory response, secretion of inflammatory cytokines and arachidonic acid and prostaglandin, protective materials for inflammation are increased ( 22 , 23 ). Lipoxin A4 (LXA4) is a metabolite for arachidonic acid that naturally exists in our body ( 23 , 24 ). LXA4 can fight inflammatory response and is a “brake signal” of inflammation ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…All in all, this study once again demonstrates the interesting challenges associated to the synthesis of iron‐containing lipoxin analogues [26] . While the biological activity of the compounds described herein did yet not fulfil our expectations, the conjugation of lipoxin‐active compounds (resolvins) with a CO‐releasing unit, however, may lead to the discovery of powerful anti‐inflammatory or neuroprotective agents in the future [27] …”
Section: Discussionmentioning
confidence: 76%